CONCEPTS OF BEING, CONSCIOUSNESS AND LANGUAGE IN TRANSFORMATION FROM EUROPEAN MIDDLE AGES TO THE ENGLISH RENAISSANCE - Kurban B. Shadmanov (Western European Studies, 2025)
In the paper, the author discusses the concepts of being, consciousness and language as notions being transformed within the historical period between the Middle Ages and the Renaissance in the English philosophical mind, and contradictions between mass nature of labor and unfair nature of the appropriation of its results matured. The moral ideals of the Middle Ages fell into a period of prolonged crisis in a philosophical and cognitive sense. Real life was lost, eluded from those philosophers who adhered to the former, oriented to God and the sacred writing of ideals. All this led to a split in the spiritual life of the late Middle Ages and opened real possibilities to a new historical period - Renaissance.
Keywords: being; West; consciousness; classical philosophy